Effect of music therapy on ICU induced anxiety and physiological parameters among ICU patients: An experimental study in a tertiary care hospital of India - Jaskirat Kaur Chahal; Preksha Sharma; Sulena; H.C.L. Rawat (Elsevier, 2021)
Background: Patients in intensive care unit (ICU) experience intense anxiety during their treatment which might also affect their physiological parameters. Aim: Study aimed to assess the effectiveness of music therapy on ICU induced anxiety and physiological parameters among intensive care unit patients in a tertiary care hospital of India.Methodology/Design: An experimental research approach with two groups pre-test post-test control design was used. 70 intensive care unit patients were randomized into two groups, experimental and conventional care group (35 in each group). The experimental group received 20 min tailored music therapy in addition to standard treatment thrice a day for continuous three days. In contrast, only standard care was provided to the other group. The socio-demographic sheet, clinical profile sheet, Zung Self Rating Anxiety Scale (SAS) and physiological parameter sheet was used to measure study parameters. Results: Music therapy was highly effective (t = 15.136 (34) p=<0.001) in reducing anxiety among experimental group subjects after the intervention whereas no change is seen in conventional care group on fourth day of the intervention. Similarly, music therapy was significantly effective in stabilizing physiological parameters among experimental group subjects during post test as compared to conventional care group. Conclusion: Music therapy is a non-invasive, non-pharmaceutical and an efficient practice to abate the ICU induced anxiety among intensive care unit patients. It also possesses the ability to stabilize the main physiological parameters of intensive care unit patients. Study recommends the use of music therapy for ICU patients to stabilize their psychological and physiological parameter.